Sheep and goat development project, Kenya. Breeding and Research (United Nations Development Programme, 1976)
As part of the Sheep and Goat Development Project being undertaken by the Government of Kenya with the assistance of the United Nations Development Programme and the Food and Agriculture Organization of the United Rations, studies were carried out to ascertain the feasibility of sheep and goat development in the arid and medium and high-potential areas. It was concluded that in the arid range areas efforts should be concentrated on crossbreeding the Dorper sheep with the local breeds, except in the areas of poorest potential, where development should be through selection of local animals. Similarly the Galla goat should be crossed with the local breeds of Small East African goat with the aim of producing an improved meat breed. In the medium and high-potential areas it was found that crossbreeding Corriedale and Romney Marsh sheep with Hampshire Down resulted in increased growth rates and improved meat production. The report outlines breeding programmes and recording systems to be followed on government research stations and large farms, and recommends the expansion of the extension services to assist smaller farmers to join the breeding programme. The establishment of a national sheep and goat breeding institution is recommended to develop the breeding programme, and the setting up of a breeders' association is suggested for the coordination of methods and activities. Much greater attention should be paid in all areas to the adoption of modern management and health protection techniques, including the provision of supplementary feed where necessary. Future research should cover breed comparison, upgrading, stocking rate and mating system trials.